Primary choriocarcinoma of the stomach. A case report - Mondragón Vera, Jhon Alberto (2022)
Primary gastric chorioadenocarcinoma (PGC) constitutes less than 1% of all gastric cancers; it is more common in men. Approximately one third of patients already have metastatic disease at the time of diagnosis. We present the case of a 70-year- old male patient, diagnosed as gastric adenocarcinoma in anthropylorus, who underwent radical distal gastrectomy. The pathological diagnosis shows an adenocarcinoma, with 85% choriocarcinomatous differentiation, 10% with areas of tubular adenocarcinoma and the remaining 5% per component suggestive of yolk sac tumor. Our patient achieved a survival of 5 months after surgery, during this time he was f ith chemotherapy. This disease continues to have a gloomy prognosis; less than 6 months.